Peran Dukungan Sosial Orang Tua dalam Menumbuhkan Growth Mindset Siswa Sekolah Dasar terhadap Mata Pelajaran Matematika - Aldino, Fals (CV. Lentera Literasi Indonesia, 2025)
This study systematically analyzes the crucial role of Parental Social Support (PSS) as a catalyst in fostering students' Growth Mindset towards Mathematics. Mathematics is often perceived as a subject measuring innate talent (Fixed Mindset), which is a major inhibitor of student motivation and achievement. Utilizing a literature review methodology, findings confirm that PSS not only correlates positively with Mathematics performance but also functions qualitatively. Appropriate emotional support from parents enables students to transform failure into constructive feedback, directly fostering Academic Buoyancy and Academic Resilience. Furthermore, effective PSS must manifest as Perceived Parental Autonomy Support, which acts as a key moderator factor. This Autonomy Support ensures students internalize the Growth Mindset by focusing on effort and strategies (Process-Based Praise) rather than solely on final results or innate ability. The main conclusion is that PSS directed at autonomy and process is a vital prerequisite for creating a Mathematics learning ecosystem capable of overcoming the stigma of difficulty and enhancing sustained Student Engagement.